Level of knowledge, attitude, and practice of family planning and associated factors among disabled persons, north-shewa zone, Amhara regional state, Ethiopia - Alemayehu Gonie Mekonnen; Alebachew Demelash Bayleyegn; Yared Asmare Aynalem; Tigist Demssew Adane; Mikyas Arega Muluneh; Meaza Asefa (BMC, 2020)
Abstract Background In Ethiopia, people with disabilities face socioeconomic disadvantages and they have a limited access to sexual and reproductive health information including family planning service. At present, however, there is a scarcity of research on the association between disability and family planning, and only limited data is available for disabled people in Ethiopia. Hence, this study assessed the level of knowledge, attitude, and practice of family planning and associated factors among disabled persons in North-shewa zone, Amhara regional state, Ethiopia. Methods A cross-sectional survey was conducted from June to October 2019. A total of 397 study participants were interviewed using a structured and pre-tested questionnaire. A multistage systematic sampling technique was employed to select study participants. Data were entered into Epi data and exported into Statistical Package for the Social Sciences (SPSS) version 21 for analysis. Logistic regression was performed to analyze the data. A significant association was declared at a p-value of less than 0.05. Results Forty-six percent of study participants were knowledgeable about family planning methods. The injectable was the most known method of modern contraception (74.8%) while withdrawal (18.1%) was the least known traditional family planning method. Fifty-five percent of our study participants had a good attitude about family planning methods and one-fourth (24.5%) of disabled persons currently utilized any method of family planning. Those having a good knowledge of family planning were 1.6 times more likely to utilize family planning methods than those having poor knowledge of family planning methods (AOR = 1.61, CI = 1.27, 16.24). Moreover, participants who completed college education were 7 times more likely to have a good knowledge of family planning methods than uneducated participants (AOR = 7.23; 95% CI = 2.28, 22.06). Conclusions In this study, the knowledge, attitude, and practice of disabled people about family planning methods were relatively low. Due attention should be given to ensure that disabled people are well informed about family planning methods through information, education, and communication activities.